Value For Money Audit Suatu Instrumen Alternatif untuk Menciptakan Akuntabilitas Publik Pemerintah Daerah - Suryo Pratolo (Journal of Accounting and Investment, 2003)
Regional autonomy has been running for almost two years, a lot of comments about the success of regional autonomy, both positive and negative. Comments indeed very necessary, but the main thing is how to make regional autonomy which is the people's demands to be more perfect and more perfect. One measure of the success of decentralization is the creation of "good governance" in which the "good governance" has many dimensions one of which is the dimension of public accountability. In this article the authors examine about public accountability in relation to the responsibilities of the regional head regulated in PP 108 in 2000. According to the author for the creation of public accountability of local government, required an auditing mechanism to support Parliament in assessing the accountability of regional heads. One alternative in the audit is "Value for Money Audit".